Pengaruh ESG Terhadap Kinerja Keuangan Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia - Benny Mohammed Edres; Rasyidi Faiz Akbar (INDO PUBLISHING, 2026)
This study aims to analyze the effect of Environmental, Social, and Governance (ESG) on the financial performance of mining companies listed on the Indonesia Stock Exchange. Financial performance is proxied by Return on Assets (ROA), while ESG is measured through three dimensions: Environmental, Social, and Governance. This research uses a quantitative approach with secondary data obtained from annual reports, sustainability reports, the Indonesia Stock Exchange, and ESG scores from BGK Foundation. The population consists of mining companies listed on the IDX, while the sample was selected using purposive sampling, resulting in 8 companies and 48 observations during 2018-2023. The analytical technique employed is panel data regression using the Fixed Effect Model with clustered standard errors. The results show that Environmental, Social, and Governance have no significant partial effect on ROA. However, the three ESG dimensions simultaneously have a significant effect on ROA. These findings indicate that ESG is more relevant when understood as an integrated strategy rather than as separate policies in explaining the financial performance of mining companies.